The Dilemma of Civic Education Online-Based Learning: Student-Teacher-Parent Relationship (STPR) on The Efforts to Improve Student's Civic Disposition During The Covid-19 Pandemic - Wardhani, Dwi Asih Triska; Fitriasari, Susan (ICHELSS: International Conference on Humanities, Education, Law, and Social Sciences, 2021)
Intensity of interaction and affordability of space between Civic Education teachers and students are decreased. It is make parents having to take further part in efforts to improve student’s civic disposition. The aim of this article is to elaborate the STPR in civic education online-based learning to improve student’s civic disposition during the pandemic. This article is the result of research with qualitative phenomenological design. Informants of this research are all teachers of Civic Education in Senior High School of Muhammadiyah Taman and representatives of students with their parents. The results showed that there was a dilemma of Civic Education online-based learning to improving student's civic disposition due to changes in STPR patterns. There needs to be an adjustment of the role between teachers and parents. The conclusion is the dilemma on efforts to improve Student's Civic Disposition during the pandemic will continue if trust, participation, and openness among parties are not improved on Civic Education Online-Based Learning. Keywords: Civic education, pembelajaran online, civic disposition, Student-Teacher-Parent-Relationship (STPR)